Smart Money? The Effect of Education on Financial Outcomes - Cole, Shawn; Paulson, Anna; Shastry, Gauri Kartini (Review of Financial Studies, 2014)
Household financial decisions are important for household welfare, economic growth, and financial stability. Yet our understanding of the determinants of financial decision making is limited. Exploiting exogenous variation in state compulsory schooling laws in both standard and two-sample instrumental variable strategies, we show that education increases financial market participation, measured by investment income and equities ownership, while dramatically reducing the probability that an individual declares bankruptcy, experiences a foreclosure, or is delinquent on a loan. Further results and a simple calibration suggest that the result is driven by changes in savings or investment behavior, rather than simply increased labor earnings.